Epidemiology of nosocomial Staphylococcus epidermidis and Acinetobacter baumannii infections in a neonatal intensive care unit - Fatemeh Nayeri; Hosein Dalili; Mamak Shariat; Nahid Farrokhzad; Kosar Abouhamzeh; Leyla Sahebi (Iranian Journal of Microbiology, 2023)
Background and Objectives: This study aimed to investigate epidemiology of Staphylococcus epidermidis (S. epidermidis) and Acinetobacter baumannii (A. baumannii) infections in neonatal intensive care unit (NICU) in a period of 8 years. Materials and Methods: This retrospective cohort study was conducted on 46 cases of nosocomial infection by S. epidermidis, and 44 neonates with A. baumannii in NICU of Valiasr hospital, Iran. Results: The trend of A. baumannii and S. epidermidis infection were as follows: 1 and 7 in 2014, 11 and 7 in 2015, 20 and 11 in 2016, 1 and 4 in 2017, 4 and 6 in 2018, 4 and 4 in 2019, 0 and 1 in 2020, and 3 and 6 in 2021-March 2022 respectively. Mortality proportion (%) in neonates with S. epidermidis and A. baumannii infection was at 8.3 and 32.1, respectively. There was a strong positive correlation between number of infected neonates in month and average of prescribed antibiotics before incidence of infection in every baby in that month. Fluconazole prescription before incidence of infection were associated with the A. baumannii infection in month too. Amikacin prescription had adjusted correlation on increasing of A. baumannii and S. epidermidis infection in month. Conclusion: It seems reducing of hospitalization duration and medication prescriptions management plays an important role in reducing of nosocomial infections.